Pasteurella multocida Septic Shock: Case Report and Literature Review - A. Aljameely; G. Wali (Case Reports in Infectious Diseases)
Pasteurella multocida is a small, Gram-negative, facultatively anaerobic coccobacillus that inhabits the normal microbiota of the respiratory tract of several animals, especially cats and dogs. By infecting humans, a wide range of clinical pictures can evolve varying from mild local cellulitis to more severe systemic diseases (e.g., meningitis, pneumonia, endocarditis, and bacteremia). Septic shock is an uncommon complication of P. multocida infection, with less than 100 cases reported in the literature. It is frequently associated with cirrhotic and immunocompromised individuals and rarely immunocompetent ones. Here, we present a case of Pasteurella multocida septic shock in an elderly man secondary to leg cellulitis with a review of the relevant literature.